Perceptions 2015: An international survey of library automation - Breeding, Marshall (Anuario ThinkEPI, 2016)
Results are presented of an online survey answered by 3,453 libraries in 63 countries between 14 November 2015 and 21 January 2016, based on their experiences with a total of 138 integrated library systems (ILS). The best products classified in the various categories analysed were Polaris, Apollo (Biblionix), Alma (Ex Libris), Symphony (SirsiDynix), WorldShare Management Services (OCLC), Koha (independent or self-managed), Library.Solution (The Library Corporation), Opals and Spydus. The original English report was published January 31, 2016 on the author´s website: http://librarytechnology.org/perceptions/2015
Keywords: Survey; Study; Report; Evaluation; Classification; Ranking; Software; Library systems; ILS; Automation products; Business; Public libraries; University libraries; Academic libraries; School libraries; Habits; Trends